Supply Chain Model for Curriculum Management Based on Thailand Qualifications Framework for Higher Education with the Internet of Things - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aimed is to develop and to evaluate the supply chain model for curriculum management based on Thailand qualifications framework for higher education with the internet of things. The research sample totaling ten experts consisted of three experts on supply chain , two experts on information technology and three experts on  electrical engineering and two expert on curriculum . All of them must have more than five years’ experience The employed research instrument is a questionnaire.  Data analysis was the average mean and standard deviation. The research was found that supply chain model for curriculum management based on Thailand qualifications framework for higher education with the internet of things consists of main components: namely main components Suppliers, University (Manufacturer), Education Customers, Consumer, Data from sensors and devices, Connectivity, cloud server and mobile app. The results from experts agreement of supply chain model for curriculum management based on Thailand qualifications framework for higher education with the internet of things was a high level. It showed that the supply chain management model could be appropriately applied in actual work settings.